2014
DOI: 10.1155/2014/916713
|View full text |Cite
|
Sign up to set email alerts
|

In VitroVitamin K3Effect on Conjunctival Fibroblast Migration and Proliferation

Abstract: Purpose. To evaluate the dose effect of vitamin K3 on wound healing mechanisms. Methods. Conjunctival fibroblasts were incubated for 24 hours. An artificial wound was made and the cells were incubated with fresh medium plus doses of vitamin K3 to be tested. Wound repair was monitored at 0, 18, 24, and 48 hours. Proliferation was measured in actively dividing cells by [3H]thymidine uptake. Six different groups were tested: group 1/no drugs added, group 2/ethanol 0.1%, group 3/vitamin K3 1 mg/L, group 4/vitamin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Unfortunately, the superoxide‐generating redox‐cycling compounds like menadione (also known as vitamin K3) and its derivatives including MSB have been reported to be cytotoxic on various mammalian cell lines with IC 50 values typically below 100 µM and, not surprisingly, these agents are proposed to be useful in anticancer therapies by taking advantage of the higher sensitivities of tumor cells . Furthermore, the ophthalmological applications of menadione may be severely limited by its adverse effects on conjunctival fibroblast proliferation and wound healing repair , the optical quality and mitochondrial integrity of crystalline lenses , the cell death processes of primary retina cells and also on cataract formation . Nevertheless, future studies with less‐cytotoxic oxidants like vitamin K1 and other naphthoquinones may provide a more acceptable and more exploitable combination.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the superoxide‐generating redox‐cycling compounds like menadione (also known as vitamin K3) and its derivatives including MSB have been reported to be cytotoxic on various mammalian cell lines with IC 50 values typically below 100 µM and, not surprisingly, these agents are proposed to be useful in anticancer therapies by taking advantage of the higher sensitivities of tumor cells . Furthermore, the ophthalmological applications of menadione may be severely limited by its adverse effects on conjunctival fibroblast proliferation and wound healing repair , the optical quality and mitochondrial integrity of crystalline lenses , the cell death processes of primary retina cells and also on cataract formation . Nevertheless, future studies with less‐cytotoxic oxidants like vitamin K1 and other naphthoquinones may provide a more acceptable and more exploitable combination.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that animals and cells cannot understand the experiment, the risk of performance bias in animal and cell experiments is low. With regard to blinding outcome assessment, the six studies conducted by Pazyar et al (2019) and Pinilla et al (2014) showed a low risk of bias, and the remaining studies were not determined by us because of insufficient information. All studies showed low risks of bias for incomplete data and selective reporting, whereas other risks of bias were unclear.…”
Section: Methodologies For the Bias Of Selected Studiesmentioning
confidence: 93%
“…By reading the full text for screening, seven articles were excluded (Supplementary Material S5) for the following reasons: four articles were not related to the effect of vitamin K on wound healing, and three articles did not report the wound healing rate, healing days, or tensile strength. Finally, six articles (including 16 studies) were eligible for meta-analysis (Amaral et al, 2014;Hemmati et al, 2014;Pinilla et al, 2014;Rush et al, 2016;Pazyar et al, 2019…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations